Flowers From Afar: Mayflowers (2021), “A las flores del Heidelberg” (1886), and Epiphytic Communities - Benitez, Christian Jil Repalda (SARE: Southeast Asian Review of English, 2025)
This essay explores the agency of the nonhuman—particularly flowers, both organic and artificial—in activating possibilities of a community. Considering the predominance of Eurowestern scholarship in the nonhuman turn, this essay takes as its critical point of departure the marginal context of the Philippines and its diaspora through selected material artistic and literary texts. The essay first examines the work Mayflowers (2021) which stages an encounter with Filipino migrants in various parts of the world through paper flowers, virtually allowing them to be in their home country during the COVID-19 pandemic. To further expound on the floral agency at work, the essay then reads the 1886 poem “A las flores de Heidelberg” by the Filipino patriot José Rizal, approaching it beyond its typical appreciation as a nostalgic ode to the Philippines through comparing it with the Thai poetic genre of nirat (นิราศ). In doing so, the flower is recognized to be a matter capable of yoking together distant subjects, allowing the unfolding an epiphytic community. To extend the prospect of the latter beyond mere nationalism, the essay takes a final turn to another community involved with the craft of making flowers in Central Thailand, juxtaposing them with the community of Filipino migrants brought together by Mayflowers, as to constellate their comparable plights toward a solidarity that is especially made visible by these nonhuman matters.